How Mindsets, Academic Performance, and Gender Predict Finnish Students' Educational Aspirations - Jenni Laurell; Khalil Gholami; Kirsi Tirri; Kai Hakkarainen (MDPI AG, 2022)
This study examined Finnish eighth graders' (N = 1136) educational aspirations and how those can be predicted by mindsets, academic achievement, and gender. Multinomial logistic regression analyses were conducted to investigate how two mindset constructs (intelligence and giftedness), domain-specific academic performance (mathematics and reading), and gender relate to students' educational aspirations on three levels (academic, vocational, and unknown). The growth mindset about giftedness was found to predict unknown aspirations, whereas the growth mindset about intelligence did not predict educational aspirations. High performance in math predicted students' academic aspirations, but performance in reading did not predict educational aspirations. Gender-related differences were found, as boys seem to have vocational aspirations, but the effect did not penetrate all schools. Lastly, students' aspirations differed between schools: from some schools, students are more likely to apply to university, while from other schools, students are more likely to apply to vocational education. Overall, the study demonstrated that a growth mindset does not directly predict academic aspirations, and the relationship between implicit beliefs and educational outcomes might be more complex than suggested.